(untitled) (Quinto Sol, 2013)
This article deals with the forms of political action of subaltern people in a particular space of peripheral Argentina: Neuquenian municipalities of the first half of the 20th Century. Even when national territories were excluded from the federal political system, the recreation in these spaces of some of the so called creole politics provides an opportunity to explore the complexity of political clientelism in those decades of Argentinian history. Furthermore, this paper pays attention to interactions between local elites and the inferior members of the clientships, observing the ways in which the latter were represented, thus shaping the relationships that both sectors kept between them. Albeit subaltern sectors of territorian Neuquen did not consolidate themselves as an autonomous political actor, it is interesting to call attention over the negotiations they were capable to maintain with local political elites. It is suggested in this paper that clientelistic practices, as the explanations constructed on them did so, contributed to shape some of the features of the Argentinian political culture of that time.